Green Political Science - O’Neill, Daniel; Bernhard, Michael (Perspectives on politics, 2023)
Each year we have the honor to publish an article version of the APSA Presidential Address. In the six years we have done this John Ishiyama is the first comparativist whose work we have featured in this capacity. He presently holds an appointment as University Distinguished Research Professor of Political Science at the University of North Texas. John has long been a fixture in the subfield of comparative politics for his contributions on democratization, political parties, and ethnic politics in both the post-Soviet region and Africa. He has also written extensively on teaching, publishing, and assessment in political science. He has published over 150 articles. And while the outlets and subject matter are too diverse to summarize succinctly, we do want to mention that “The Politics of Intercountry Adoption: Explaining Variation in the Legal Requirements of Sub-Saharan African Countries,” coauthored with Marijke Breuning, won the 2010 APSA Heinz Eulau Award for Best Journal Article published in Perspectives on Politics during the previous year (2009).